Childhood Neuroendocrine Tumors of Appendix: Suggested Approach and Management - Muhammad Matloob Alam; Abdulrhman Alathaibi; Mohamed Magdi Refai; Abdulaziz Alsaedi; Muhammad Usman Tariq (The Korean Society of Pediatric Hematology-Oncology, 2023)
Appendiceal neuroendocrine tumors (NET) although rare, but the most common tumors of the gastrointestinal tract in children and adolescents. NET of the appendix is typically undiagnosed preoperatively, are usually not associated with specific neuroendocrine symptoms, and a high percentage are initially identified by pathologists. For well-differentiated tumors of ＜1 cm and complete (R0) resection, no follow-up is required. Unlikely, tumor size ＞2 cm or tumor with high-risk features confer a relevant risk of recurrence and further imaging and surgical procedures are warranted. No consensus, clear recommendation or management guidelines are available for the management of appendiceal NET in children. Herein, current article will provide an overview of literature and suggested guidelines for evaluation and management of childhood neuroendocrine tumors of appendix.